Classe inversée en sciences de la vie et de la Terre. Des difficultés spécifiques au dispositif ? - Marion van Brederode (Nantes Université, 2022)
This article presents the implementation of a flipped classroom by a teacher in the context of teaching about the chemical digestion of food in humans in a French class with pupils 12-13 years old. A session was filmed, the pupils' productions and work support collected, the interactions between the pupils, who work in groups, were recorded and transcribed, and then semi-directive self-confrontation interviews were conducted with the teacher and the pupils, following the traces of their activity. The analysis of this corpus is framed by theoretical supports borrowed from the sociology of the teaching profession, from the analysis of the activity and from didactics, in particular the didactics of life and earth sciences. It shows that the reverse class system does not in itself resolve some of the obstacles that traditional teaching also faces. The choice of the capsule and its articulation with the other elements of the course raise questions about the teaching aids, the effects of which (possibly disruptive) on pupils' learning should be studied. In addition, the use of group work, which is fairly systematic in flipped classroom system, provides an opportunity to question the difficulties that this teaching method may pose for pupils and teachers, in particular the way in which it may lead to misunderstandings about the aims of the work requested.